Template Based Electrochemical Synthesis of Copper (Cu) Nanowires as CH2Cl2 Sensor. Issue 204 (2nd January 2020) - Gupta, Jyoti; Arya, Sandeep; Singh, Anoop; Verma, Sonali; Sharma, Asha; Singh, Bikram; Tomar, Amit
Abstract: In this work, Copper (Cu) nanowires were synthesized electrochemically from aqueous acidic solution of 1 M copper (II) sulfate (CuSO4 ·5H2 O) on a copper substrate by template-assisted electrodeposition method. The electrodeposition was conducted at room temperature and the length of nanowires was controlled by adjusting the deposition time. Different Structural and morphological characteristics were examined using X-ray diffraction (XRD), field emission scanning electron microscope (FESEM) and energy dispersive X-ray spectroscopy (EDX) that confirmed the successful synthesis of Cu nanowires. Moreover, the synthesized Cu nanowires were investigated for CH2 Cl2 chemical sensing using different electrochemical techniques. The results showed that Cu nanowires can sense CH2 Cl2 very effectively.